Neuropathological correlations of 18F-florzolotau PET in a case with Pick’s disease - Hisaomi Suzuki; Manabu Kubota; Shin Kurose; Kenji Tagai; Hironobu Endo; Mitsumoto Onaya; Yasuharu Yamamoto; Naruhiko Sahara; Masahiro Ohgidani; Chie Haga; Hiroya Hara; Haruhiko Akiyama; et al. (EJNMMI Research)
Abstract Background Pick’s disease (PiD) is classified as frontotemporal lobar degeneration with pathological tau aggregates. Positron emission tomography (PET) with 18F-florzolotau provides high-contrast imaging of diverse tau fibrils. While our previous work demonstrated the detectability of three repeat (3R) tau pathology by 18F-florzolotau PET in an autopsy-confirmed PiD patient, its potential for quantitative assessment of 3R tau aggregates in living individuals remains unclear. In this study, we analyzed correlations between in vivo 18F-florzolotau retentions and postmortem neuropathological data across brain regions in the same case with PiD. Case presentation The patient was 60 years of age at the time of death and had been diagnosed with behavioral variant frontotemporal dementia. The patient underwent 18F-florzolotau PET one year prior to death and was given the pathological diagnosis of PiD by brain autopsy. Regional tau pathology was assessed using Bodian’s silver staining and immunohistochemistry with a monoclonal antibody (AT8). Histopathological assays revealed abundant intraneuronal Pick bodies along with neuropil threads in frontotemporal and other brain areas. In the cerebral cortex, AT8-positive areas exhibited a significant positive correlation with 18F-florzolotau binding in the corresponding regions (Pearson’s r = 0.81, p < 0.001) estimated as standardized uptake value ratio corrected for partial volume effect. In contrast, no such associations were found in subcortical structures. Furthermore, a substantial proportion of Pick bodies displayed fluorescence co-labelled with florzolotau and AT8 antibodies. Conclusions Collectively, the present findings support the capability of 18F-florzolotau PET for the in vivo quantification of 3R tau fibrils.